Study on emerging risk factors of acute myocardial infarction patients in Kumaon region of Uttarakhand, India - Gupta, Ashu; Joshi, Arun; Kumar, Ashok; Singh, Paramjeet (International Journal of Advances in Medicine, 2018)
Background: Cardiovascular disease is a major global health problem reaching epidemic proportions. Along with the developed nations, underdeveloped and developing countries are now facing this burden. Keeping this in mind various emerging risk factors in patients with documented evidence of acute myocardial infarction attending a tertiary care hospital in the Kumaon region of Uttarakhand were studied. Methods: This study is a prospective study done in the department of Medicine, Sushila Tiwari Government Hospital, Haldwani over a period of 2 years. Patients were enrolled from the Medical Emergency/ OPD who had documented evidence of Acute Myocardial Infarction. Informed consent was taken from each study subject. Results: The mean age was 54.27 years (SD- 13.062). Among the risk factors, high triglyceride is significantly higher in younger patients as compare to older patients. Lipid profile distribution when they compare to any addiction, it has been found in the study that LDL is significantly higher in those who were having any addiction. Hypertension was significantly higher in patients who smoke (p=0.04). The major contributing risk factor was any addiction (smoking, alcohol, tobacco consumption in any form) followed by dyslipidemia. Conclusions: The challenge is to develop appropriate strategies to prevent coronary artery diseases and promote healthy lifestyles.